Binary mixtures of ionic liquids in aqueous solution: towards an understanding of their salting-in/salting-out phenomena - Neves, Catarina M. S. S. (2020)
The order of the salting-in or salting-out inducing ability of ions on the aqueous solubility of macromolecules in aqueous solutions is known as the Hofmeister series. Taking into account that ionic liquids (ILs) are constituted by ions, they can exert similar effects on the solubility of other ILs in aqueous media. In order to expand the knowledge on the salting-in/-out ability of ILs, experimental studies on the solubility of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonylimide) in water in presence of other IL/salts were conducted at 298.15 K at atmospheric pressure. Both the impact of the anion and cation of the IL were evaluated with the following ILs/salts: 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hydrogensulfate, cholinium bis(trifluoromethylsulfonyl)imide, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide, in a wide composition range. As happens with common salts, both salting-in and salting-out effects exerted by ILs were observed, with a higher impact exerted by the IL anion on the salting-out phenomenon. These data allow to better understand the ILs impact when designing liquid-liquid separation processes.